2020
DOI: 10.14712/fb2020066030086
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Factor as an Option for Managing the COVID-19 Pandemic

D. Viza,
G. Pizza,
C. De Vinci
et al.

Abstract: Covid-19 or SARS-CoV-2, a new RNA virus with high infectivity, and seemingly low mutability, which appeared in 2019 in the Wuhan province of China, has created a pandemic with dire consequences. At the end of May 2020, it became the first cause of mortality. As no treatment or vaccine may become available before many months, and because occurrence of similar pandemics is only a matter of time, arguments are presented here for testing the effect of transfer factor (TF), an immunomodulator devoid of toxicity, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The spread of the disease is also exacerbated by viral shedding, a common biological process observed in symptomatic patients (Long et al, 2021). The COVID-19 course is influenced not only by host immune system variability (Paces et al, 2020), but an important factor is also genetic predisposition, which has been shown to be a predictor of both susceptibility to infection and COVID-19 severity (Kostrouch, 2020;Viza et al, 2020;Hubacek, 2021a;Delanghe and Speeckaert, 2022). Pati et al (2021) reported the results of an in silico study, which identified a potential association between the functional CD14 polymorphism rs2569190 (C-159→T, C-260→T relative to the translation start site) and increased susceptibility to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of the disease is also exacerbated by viral shedding, a common biological process observed in symptomatic patients (Long et al, 2021). The COVID-19 course is influenced not only by host immune system variability (Paces et al, 2020), but an important factor is also genetic predisposition, which has been shown to be a predictor of both susceptibility to infection and COVID-19 severity (Kostrouch, 2020;Viza et al, 2020;Hubacek, 2021a;Delanghe and Speeckaert, 2022). Pati et al (2021) reported the results of an in silico study, which identified a potential association between the functional CD14 polymorphism rs2569190 (C-159→T, C-260→T relative to the translation start site) and increased susceptibility to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Folia Biologica, Viza and colleagues suggest transfer factor as a potential option for managing the COVID-19 pandemic (Viza et al, 2020). Transfer factor, an activity identified in activated immune cells, which has modulatory effects on cell-mediated immunity, belongs to small regulatory proteins in a broader sense.…”
mentioning
confidence: 99%
“…Transfer factor is a well-suited target for focused research on Covid-19 (SARS-CoV-2) and similar infections, as suggested by Viza et al (2020).…”
mentioning
confidence: 99%